Exercise and Vitamin D Supplementation Modify Spleen Morphology in Lean, but not, in Monosodium-Glutamate-Obese Rats - Zoé, Maria Guareschi; Vanessa, Marieli Ceglarek; Patrick, Fontes Rodrigues; Luiz, Pierre Huning; Cintia, Festinalli; João, Paulo de Arruda Amorim; Sabrina, Grassiolli (Journal of Spleen And Liver Research, 2019)
An experimental study examines how exercise and vitamin D supplementation affect spleen morphology in lean versus MSG‑obese rats, discussing immunologic implications.
Keywords: Swimming; spleen; vitamin D; obesity; histomorphometry